Regulation of transcription in plants: Mechanisms controlling developmental switches - Kaufmann, K.; Pajoro, A.; Angenent, G.C.
Unlike animals, plants produce new organs throughout their life cycle using pools of stem cells that are organized in meristems. Although many key regulators of meristem and organ identities have been identified, it is still not well understood how they function at the molecular level and how they can switch an entire developmental programme in which thousands of genes are involved. Recent advances in the genome-wide identification of target genes controlled by key plant transcriptional regulators and their interactions with epigenetic factors provide new insights into general transcriptional regulatory mechanisms that control switches of developmental programmes and cell fates in complex organisms. © 2010 Macmillan Publishers Limited. All rights reserved.
Keywords: ANIMALS; GENE EXPRESSION REGULATION, PLANT; MERISTEM; PLANT PROTEINS; PLANTS; TRANSCRIPTION FACTORS